A genetic analysis of the suppressor 2 of zeste complex of Drosophila melanogaster. - Wu, C.; Howe, M. (Genetics, 1995)
The zeste1 (z1) mutation of Drosophila melanogaster produces a mutant yellow eye color instead of the wild-type red. Genetic and molecular data suggest that z1 achieves this change by altering expression of the wild-type white gene in a manner that exhibits transvection effects. There exist suppressor and enhancer mutations that modify the z1 eye color, and this paper summarizes our studies of those belonging to the Suppressor 2 of zeste complex [Su(z)2-C]. The Su(z)2-C consists of at least three subregions called Psc (Posterior sex combs), Su(z)2 and Su(z)2D (Distal). The products of these subregions are proposed to act at the level of chromatin. Complementation analyses predict that the products are functionally similar and interacting. The alleles of Psc define two overlapping phenotypic classes, the hopeful and hapless. The distinctions between these two classes and the intragenic complementation seen among some of the Psc alleles are consistent with a multidomain structure for the product of Psc. Psc is a member of the homeotic Polycomb group of genes. A general discussion of the Polycomb and trithorax group of genes, position-effect variegation, transvection, chromosome pairing and chromatin structure is presented.